Discovery of Ulmaceae-feeding Tischeriidae (Lepidoptera, Tischerioidea), Tischeria ulmella sp. nov., and the first report of the Quercus-feeding T. naraensis Sato in China - Xu, Jiasheng; Dai, Xiaohua; Liao, Chengqing; Diškus, Arūnas; Stonis, Jonas R. (Zootaxa, 2018)
We provide the first report of Tischeriidae on Ulmaceae, a novel host-plant family, and describe Tischeria ulmella Xu & Dai, sp. nov., a new species discovered in the Yellow River Scenic Area of Zhengzhou (Henan Province, China), feeding on Ulmus pumila L. We also provide a redescription of the Quercus-feeding Tischeria naraensis Sato discovered in China for the first time. Both species are illustrated with photographs of the adults, male and female genitalia, and the leaf mines.